Legal doctrine as a means of constructing legal reality - N. V. Razuvaev (Теоретическая и прикладная юриспруденция)
The article deals with the problem of the law-making meaning of legal doctrine. According to the author, the doctrine is an internally coherent segment of juridical science, with the ability to not only provide the juridical community generally accepted interpretation of legal phenomena, but also to establish mandatory for members Society of behavior patterns. As the legal science in General, the doctrine is a collection of semiotic forms (texts), which construct the juridical reality. As a source of law doctrine creates legal rules on the basis of typification of subjective rights and responsibilities of individuals. Implementation of regulatory functions is carried out by doctrine, according to the author, in three ways, namely, through legislation, jurisprudence and law enforcement practitioners.